Dithienylethene-bridged difluoroboron β-diketonate dyes: Optical switching behaviors and triple sensing for volatile amine vapors. (August 2020) - Li, Ziyong; Pei, Yingying; Hou, Siteng; Dai, Yijie; Liu, Duoduo; Zhu, Junli; Zhu, Yan-Ping; Liu, Xianming
Abstract: Developing new visible light-triggered NIR photochromic sensors for the accurate detection of volatile amine vapors in the solid state is highly desirable. Herein, three novel dithienylethene-bridged difluoroboron β-diketonate dyes Di-BF 2 bdk-DTE1-Di-BF 2 bdk-DTE3, in which BF2 bdk group not only functions as electron acceptor but also responds to amine vapors, have been developed. Upon alternating irradiation with blue light (460–470 nm) and near-infrared light (760–770 nm), they displayed excellent NIR photochromism and fluorescent switching behaviors in toluene and in the PMMA film. Moreover, they showed an unprecedented triple sensing performance for volatile n -propylamine vapor in the PMMA film state (fluorescent-colorimetric-colorimetric). Therefore, they would be utilized as triple sensing membranes for selective detection towards volatile primary or secondary amine vapors in environmental and biological systems. Graphical abstract: Image 1 Highlights: Three novel dithienylethene-bridged difluoroboron β-diketonate dyes were developed. They displayed excellent NIR optical switching behaviors in toluene and PMMA film upon irradiation with blue/NIR light. They showed an unprecedented triple sensing performance for volatile  n -BuNH2  vapor in the PMMA film.